Crystal engineering of selected phenolic acids - Amombo Noa, Francoise Mystere (Cape Peninsula University of Technology, 2014)
Crystal engineering based upon acid: base compounds have been studied in this thesis. Selected phenolic acids such as: vanillic acid (VA), phenylacetic acid (PAA), 4-hydroxyphenylacetic acid (HPAA), 3-chloro-4-hydroxyphenylacetic acid (CHPAA), caffeic acid (CFA), p-coumaric acid (pCA), trans-ferulic acid (tFER), 2-phenylpropionic acid (PPA) and 2-phenylbutyric acid (PBA) were the main compounds investigated. These phenolic acids have formed co-crystals/co-crystal hydrates, salts/salt hydrates and hybrid salt-co-crystals with acridine (ACRI), caffeine (CAF), cinchonidine (CIND), isonicotinamide (INM), isonicotinic acid (INA), nicotinamide (NAM), quinidine (QUID), quinine (QUIN), theobromine (THBR), theophylline (THPH) and urea (U). The two racemic compounds 2-phenylpropionic acid (PPA) and 2-phenylbutyric acid (PBA) were used to study chiral discrimination leading to the understanding of separation enantiomers. Compounds were prepared in different solvents (alcohols, ketone and distilled water) to investigate the relationship between solvents used and the crystalline product obtained. (If there is any effect on the crystalline compound obtained by changing the solvent). The structures were elucidated using single crystal X-ray diffraction. Ground products of obtained compounds were characterized by powder X-ray diffraction (PXRD). Thermal analyses like thermogravimetry (TG), differential scanning calorimetry (DSC) and hot stage microscopy (HSM) were used for the determination of thermal character of the new compounds. IR was also performed to characterize the new compounds. Non-isothermal TG was utilised to obtain kinetic parameters for the water and the methanol release in (pCA−)(QUIN+)•pCA•MeOH•H2O. A selective experiment was done in which quinidine and quinine were used to compete between selected phenolic acids (PAA and HPAA). viii The comparison of the crystal structures determined showed that, changing the phenolic acid while using the same co-crystal former has a significant effect on the type of compounds obtained. The obtained crystal structures were either co-crystal/co-crystal hydrates, salts/salt hydrates or hybrid salt-co-crystals which formed network via means of supramolecular interactions.
Thesis (MTech (Chemistry))--Cape Peninsula University of Technology, 2014
Keywords: Crystal engineering; Thermal analysis; Kinetic; Phenols; Crystals